Perubahan Pendidikan Islam - Damhudi, Dedi; Wanto, Deri (Yayasan Literasi Kita Indonesia, 2023)
Islam apart from being a religion is also a means of education for its people. Islam provides guidelines that need to be considered by its people as a way to achieve salvation. In its history, Islamic civilization cannot be separated from education, starting from the time of the Prophet Muhammad SAW, periodKulafaur Rashidun,the Umayyad empire, to its peak during the Abbasid empire. At the peak of the heyday of Islam, at that time Islamic education was experiencing its heyday as seen from the many world-class Islamic thinkers, one of them Al-Gazali, Ibn Sina, Ibn Khaldun, Al Kindi to Al Khawarizmi. All of these Islamic thinkers have influenced the face of world scholarship, whose ideas are still used and their truth is acknowledged today. With the changes in Islamic education that have occurred at this time, it is hoped that there will be values that can be taken as lessons for Muslims today, as well as being a motivation for Islamic scholars to be able to express their thoughts.